P18.06 Early antiretroviral therapy and pre-exposure prophylaxis for hiv prevention among female sex workers in cotonou, benin: early follow-up and adherence data. (13th September 2015) - Guédou, FA; Béhanzin, L; Geraldo, N; Goma Mastétsé, E; Singbo, N; Sossa, JC; Zannou, MD; Alary, M
Abstract : Introduction: To assess the feasibility and usefulness of integrating treatment as prevention (TasP) and pre-exposure prophylaxis (PrEP) with Truvada ® to the combination prevention package offered to female sex workers (FSWs) in Cotonou, we are currently carrying out a demonstration project on these two HIV preventive strategies among FSWs. Methods: We are currently recruiting 100 HIV-infected FSWs for TasP and 250 HIV-negative FSWs for PrEP (one-year recruitment period, followed by an additional one year of follow-up). The actual recruitment visit is preceded by a screening visit two weeks earlier in order to determine the HIV status and assess other eligibility criteria. Through follow-up visits at day 14 and then quarterly, we closely monitor treatment adherence, using various tools including a pill count strategy. For the latter, we ask participants to bring in their bottles of medication at each visit. We report here on the first five months of the clinical phase of the study. Results: From 18 th september 2014 to 28 th February 2015, we screened 154 FSWs and out of them, 85 and 34 were recruited in the PrEP and TasP arms, respectively. Median age of the participants was 34 years and 38% were from Benin, whereas the other were from surrounding countries. To 28 th February, the overall retention rate in the study was 100% for TasP and 85% for PrEP. Most drop-outs were due to mobility and leaving the sex trade. Adherence to PrEP was 84% according to pill count. Conclusion: The retention rate in the study is encouraging so far. Adherence levels, although estimated through a simple method that could lead to overestimations, could be improved and a multi-faceted adherence education program is now implemented. The availability of Truvada ® blood levels will allow an objective assessment of adherence, a highly crucial parameter for the success of eventual PrEP programs. Disclosure of interest statement: This study is funded by the Bill and Melinda Gates Foundation, and Truvada® for pre-exposure prophylaxis is provided free of charge by Gilead Sciences, Inc.